2020
DOI: 10.1186/s12890-020-01187-7
|View full text |Cite
|
Sign up to set email alerts
|

Lung and general health effects of Toll-like receptor-4 (TLR4)-interacting SPA4 peptide

Abstract: Background: A surfactant protein-A-derived peptide, which we call SPA4 peptide (amino acids: GDFRYSDGTPVNYTNWYRGE), alleviates lung infection and inflammation. This study investigated the effects of intratracheally administered SPA4 peptide on systemic, lung, and health parameters in an outbred mouse strain, and in an intratracheal lipopolysaccharide (LPS) challenge model. Methods: The outbred CD-1 mice were intratracheally administered with incremental doses of SPA4 peptide (0.625-10 μg/g body weight) once ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…It has been shown that it can inhibit LPS-stimulated inflammatory responses, migration and invasion of colon cancer SW480 [ 157 ]. Similar results were also reported in the lung cancer [ 158 , 159 ].…”
Section: Tlrs Antagonistssupporting
confidence: 90%
“…It has been shown that it can inhibit LPS-stimulated inflammatory responses, migration and invasion of colon cancer SW480 [ 157 ]. Similar results were also reported in the lung cancer [ 158 , 159 ].…”
Section: Tlrs Antagonistssupporting
confidence: 90%
“…To understand the biological relevance of results from in vitro experiments, we included a mouse model of intratracheal E. coli LPS challenge that induces lung inflammation ( 30 ). Our previously published results demonstrated that the intratracheally administered SPA4 peptide on its own did not induce toxicity or inflammation but suppressed the LPS-induced lung inflammation, edema, and biochemical markers of tissue injury in mice ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…To understand the biological relevance of results from in vitro experiments, we included a mouse model of intratracheal E. coli LPS challenge that induces lung inflammation ( 30 ). Our previously published results demonstrated that the intratracheally administered SPA4 peptide on its own did not induce toxicity or inflammation but suppressed the LPS-induced lung inflammation, edema, and biochemical markers of tissue injury in mice ( 30 ). As expected, the changes in BALF cell populations (increase in CD11b hi Gr1 hi , Gr1 + CD11b hi , Gr1 + CD11b med , CD11b + CD11c − , CD11b + CD11c + IAIE − CD14 − , CD11b + CD11c − IAIE lo CD14 lo-med , CD11b − CD11c + IAIE hi CD 14 lo-med , CD11b + CD68 lo F4/80 lo-med , and CD11b + CD14 − cell populations and a slight alteration in CD11b − CD11c − IAIE hi CD14 lo-med and IAIE + CD11c hi CD103 hi CD123 hi cell populations) were noted in LPS-challenged mice.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mice administered an SP-A-related peptide, SPA4, displayed a reduced inflammatory response following intratracheal LPS administration [127] as well as improved symptom and histological scores, increased bacterial clearance and reduced cytokine levels in mice infected with Pseudomonas aeruginosa [128].…”
Section: Pulmonary Infectionsmentioning
confidence: 98%
“…Similarly, in both animal models [71,130] and in patients suffering acute asthma attacks [74,131], exogenous surfactant was associated with short-term improvements in lung function. There is also the potential of supplementing with collectins, as one research group has shown in several mouse models that administration of SPA4, an SP-A-related protein, was able to significantly improve the response to infection in a mouse model [127,128]. This highlights the importance of characterising the type, extent and cause of the surfactant dysfunction observed in a particular lung disease to best target the pathology.…”
Section: Supplementing the Pulmonary Surfactant Poolmentioning
confidence: 99%